Disassembly system modeling and design with parts selection for cost, recycling and CO2 saving rates using multi criteria optimization. (January 2016) - Igarashi, Kento; Yamada, Tetsuo; Gupta, Surendra M.; Inoue, Masato; Itsubo, Norihiro
Abstract: Environmental issues in supply chains have been serious for not only the reduction of CO2 emissions but also for material starvation. End-of-life assembly products at recycling factories should be disassembled environmentally and economically in consideration of not only low carbonization but also of material circulation. Parts with higher recycling and CO2 saving rates should be selected and manually disassembled; however, the manual disassembly brings a higher cost, instead of disposing of the parts. Moreover, this parts selection also affects a disassembly line balancing. This study proposes a simple and practical modeling and design of multi criteria optimization for lower disassembly cost, higher recycling, and CO2 saving rates by an environmental and economic parts selection, and subsequent disassembly line balancing.